The Distribution of Investment Risk in Defined Benefit Pension Plans: A Reconsideration - Hyatt, Douglas; Pesando, James (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1996)
The "textbook " description is that members of defined benefit pension plans bear no investment risk, in sharp contrast to members of defined contribution plans. Yet formal or informal bargaining may focus on the size of required employer contributions to a defined benefit plan. If at least some of the costs of such employer contributions are shifted back to workers, then members of defined benefit plans do bear investment risk. We utilize three sources of empirical evidence (a survey of pension specialists, econometric analysis, and case studies) to support the proposition that employees do bear at least some of the investment risk associated with pension fund performance. Poor fund performance leads to larger employer contributions to maintain the defined benefit obligation and this in turn leads to lower levels of other forms of compensation. We conclude that riskshifting does occur, in at least some plans, and that the textbook distinction is overstated.